Traumatic Brain Injury Upregulates Phosphodiesterase Expression in the Hippocampus - Wilson, Nicole M.; Titus, David J.; Oliva, Anthony A.; Furones, Concepcion; Atkins, Coleen M. (Frontiers in Systems Neuroscience, 2016)
Traumatic brain injury (TBI) results in significant impairments in hippocampal synaptic plasticity. A molecule critically involved in hippocampal synaptic plasticity, 3',5'-cyclic adenosine monophosphate (cAMP), is downregulated in the hippocampus after TBI, but the mechanism that underlies this decrease is unknown. To address this question, we determined whether phosphodiesterase (PDE) expression in the hippocampus is altered by TBI. Young adult male Sprague Dawley rats received sham surgery or moderate parasagittal fluid-percussion brain injury. Animals were analyzed by western blotting for changes in PDE expression levels in the hippocampus. We found that PDE1A levels were significantly increased at 30 min, 1 hr and 6 hr after TBI. PDE4B2 and 4D2 were also significantly increased at 1, 6 and 24 hr after TBI. Additionally, phosphorylation of PDE4A was significantly increased at 6 and 24 hr after TBI. No significant changes were observed in levels of PDE1B, 1C, 3A, 8A or 8B between 30 min to 7 days after TBI. To determine the spatial profile of these increases, we used immunohistochemistry and flow cytometry at 24 hr after TBI. PDE1A and phospho-PDE4A localized to neuronal cell bodies. PDE4B2 was expressed in neuronal dendrites, microglia and infiltrating CD11b+ immune cells. PDE4D was predominantly found in microglia and infiltrating CD11b+ immune cells. To determine if inhibition of PDE4 would improve hippocampal synaptic plasticity deficits after TBI, we treated hippocampal slices with rolipram, a pan-PDE4 inhibitor. Rolipram partially rescued the depression in basal synaptic transmission and converted a decaying form of LTP into long-lasting LTP. Overall, these results identify several possible PDE targets for reducing hippocampal synaptic plasticity deficits and improving cognitive dysfunction acutely after TBI.